2022
DOI: 10.1371/journal.pbio.3001904
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the boundaries of behavioral analysis could aid psychiatric drug discovery

Abstract: Drug discovery for psychiatric conditions is stagnating. Behavioral changes could be used as a primary phenotypic screen for new drug candidates, if enough useful data can be generated from behavioral models. Could machine learning be the answer to extracting the data we need?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Behavior analysis/valuation is a concept derived from psychology and medicine, which is used to predict and treat diseases [ 17 ]. Behavior analysis includes many applications and methods, some of which are carried out from the medical view [ 18 ], and some of which use data mining methods, including wavelet neural network [ 19 ] and recurrent neural network [ 20 ].…”
Section: Related Workmentioning
confidence: 99%
“…Behavior analysis/valuation is a concept derived from psychology and medicine, which is used to predict and treat diseases [ 17 ]. Behavior analysis includes many applications and methods, some of which are carried out from the medical view [ 18 ], and some of which use data mining methods, including wavelet neural network [ 19 ] and recurrent neural network [ 20 ].…”
Section: Related Workmentioning
confidence: 99%
“…[20][21][22][23][24][25] Recent discoveries in the field of neuroeconomics have begun to push the boundaries on what can be investigated in animal research, offering novel approaches using clever tasks to extract hidden features of behavior in order to study interactions between mood and decision-making in a manner that is biologically tractable and readily translatable across species. [26][27][28][29][30][31][32][33] The sunk cost bias has been extensively studied in the human psychology literature but has been repeatedly ascertained that this phenomenon is unique to humans. 34,35 Using a neuroeconomic approach, it was recently discovered for the first time evidence that rodents are capable of demonstrating sensitivity to sunk costs in a manner that is directly matched to human behavior using a novel set of neuroeconomic decision-making tasks recently developed for use across species.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Furthermore, the biological and psychological mechanisms through which antidepressant treatments, including newer rapid-acting drugs like ketamine, exert their effects are not well understood. 33,[40][41][42] Here, we tested the effects of stress using a well-established animal model of depression (the chronic social defeat stress paradigm) on mice tested in a novel neuroeconomic decision-making paradigm (the Restaurant Row task) in which mice forage for food rewards of varying costs while on a limited budget. 36,43 We found that exposure to a psychosocial stressor produced a robust increase in sensitivity to sunk costs without affecting gross changes in locomotion, motivation, body weight, or feeding behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…information processing capable of resolving behavior into discretely measurable computational units in a manner that is biologically tractable and readily translatable across species [23][24][25] .…”
mentioning
confidence: 99%
“…Such approaches would be critically informative if applied toward translational studies of diabetes. Recent insights from neuroeconomic principles offer novel approaches to investigate decision-making information processing capable of resolving behavior into discretely measurable computational units in a manner that is biologically tractable and readily translatable across species [23][24][25] .…”
mentioning
confidence: 99%